Work hour mismatch and job mobility: Adjustment channels and resolution rates - Michael C. Knaus; Steffen Otterbach (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper analyses the role of job changes in overcoming work hour constraints and the work hour mismatches resulting from these constraints (i.e., differences between actual and desired work hours). Building on previous findings that job change increases the flexibility of actual work hours, the study addresses two as yet neglected questions in the context: (i) How do changes in desired work hours, in addition to changes in actual work hours, contribute to the resolution of thesemismatches? (ii) Does the increased flexibility help actually to resolve work hour mismatches? We exploit information about the magnitude of the prevailing mismatch to improve both the credibility and interpretation of the results. We find that job change increases the probability of resolving work hour mismatches, but far less than expected with free choice of hours across jobs. Instead, large fractions of workers either stay or switch into overemployment. We thoroughly investigate the robustness and heterogeneity of our results.
Keywords: J21; J22; 330; Work Hour Constraints; Work Hour Mismatch; Job Mobility; Desired Work Hours; Germany